The amphibian skin‐associated microbiome across species, space and life history stages - Jordan G. Kueneman; Laura Wegener Parfrey; Douglas C. Woodhams; Holly M. Archer; Rob Knight; Valerie J. McKenzie (Molecular Ecology, 2014)
Skin‐associated bacteria of amphibians are increasingly recognized for their role in defence against pathogens, yet we have little understanding of their basic ecology. Here, we use high‐throughput 16 S r RNA gene sequencing to examine the host and environmental influences on the skin microbiota of the cohabiting amphibian species A naxyrus boreas, P seudacris regilla, T aricha torosa and L ithobates catesbeianus from the C entral V alley in C alifornia. We also studied populations of R ana cascadae over a large geographic range in the K lamath M ountain range of N orthern C alifornia, and across developmental stages within a single site. Dominant bacterial phylotypes on amphibian skin included taxa from B acteroidetes, G ammaproteobacteria, A lphaproteobacteria, F irmicutes, S phingobacteria and A ctinobacteria. Amphibian species identity was the strongest predictor of microbial community composition. Secondarily, within a given amphibian species, wetland site explained significant variation. Amphibian‐associated microbiota differed systematically from microbial assemblages in their environments. Rana cascadae tadpoles have skin bacterial communities distinct from postmetamorphic conspecifics, indicating a strong developmental shift in the skin microbes following metamorphosis. Establishing patterns observed in the skin microbiota of wild amphibians and environmental factors that underlie them is necessary to understand skin symbiont community assembly, and ultimately, the role skin microbiota play in the extended host phenotype including disease resistance.